Aluminum Casting Laboratory Implementation to Build Competence of Teacher Candidate of Vocational High School - Arianto Leman Soemowidadgo; Widarto Widarto; Tiwan Tiwan; Aan Ardian; Silvia Sianipar (Jurnal Dinamika Vokasional Teknik Mesin, 2020)
This study aimed at implementing Casting Laboratory model to build competence of teacher candidate of Vocational High School of Mechanical Engineering Study Program. The study is conducted by try out application approach. The procedure comprised of equipment preparation, layout arrangement, practice and evaluation. Data were collected by observation. The research subject was two classes of third semester bachelor students of MEED YSU who enrolled in Advanced Engineering Materials practical course. The two classes consist of 4 teams and within each team there were 4 groups. The practical work was carried out 2 times. The results show that the Casting Laboratory model has met all of the qualification of a learning facility to build student competence in unpressurized casting process. Among these competencies are ability in pattern making, sand preparation, sand-mold making, planning raw materials and smelting process, handling and pouring of molten metal, disassembling and cleaning, and evaluating the cast. The Casting Laboratory layout has qualified as work area for casting practice. The layout makes supervision and movement of workers and materials easy. Tools and equipment are fitting and adequate. The Laboratory model for aluminum casting is effective and efficient to develop competence in casting.Penelitian ini bertujuan menerapkan model Laboratorium Pengecoran untuk membentuk kompetensi calon guru Sekolah Menengah Kejuruan Program Studi Teknik Mesin. Penelitian dilakukan dengan pendekatan uji aplikasi. Prosedur terdiri dari persiapan peralatan, pengaturan tata letak, praktik dan evaluasi. Data dikumpulkan dengan observasi. Subjek penelitian adalah adalah 2 kelas mahasiswa semester tiga program S1 teknik mesin MEED YSU yang mengikuti praktik bahan teknik lanjut, terdiri dari 4 tim dan masing-masing tim dibagi menjadi 4 kelompok. Praktikum dilaksanakan dua kali. Hasil penelitian menunjukkan bahwa model Laboratorium Pengecoran telah memenuhi syarat sebagai fasilitas pembelajaran untuk membentuk kompetensi siswa dalam proses pengecoran tanpa tekanan. Kompetensi yang dibentuk adalah kemampuan dalam membuat pola, menyiapkan pasir, membuat cetakan pasir, merencanakan bahan baku dan proses melebur, menanganani dan menuangkan logam cair, membongkar dan membersihkan, serta mengevaluasi produk pengecoran. Tata letak Laboratorium Pengecoran telah memenuhi syarat sebagai area kerja untuk praktik pengecoran. Ini memberi kemudahan dalam pengawasan dan pergerakan orang dan barang. Alat dan peralatan sudah sesuai dan memadai. Model laboratorium untuk pengecoran aluminium efektif dan efisien untuk mengembangkan kompetensi pengecoran.